Species composition and distribution of birds in the area of Kyzyl airport (Republic of Tyva, Russia) and their impact on the ornithological situation - Tatyana P. Archimayeva; D. K. Kuksina; A. N. Kuksin; A. T. Saaya (Юг России: экология, развитие, 2024)
Aim. Study and identification of species composition and actual location of birds on the territory of the Kyzyl airport and in the airspace above it throughout the year and assessment of the intensity of the ornithological situation in order to ensure flight safety.The study of avifauna within the airport area within a radius of 15 km was carried out throughout a calendar year using the method of integrated route accounting and stationary observations on the runway. Statistical processing of the field materials was carried out using the Microsoft Excel program.In total, a fairly high species diversity was revealed within the airport territory – 76 species in zone I – R =2,5 km and 199 species in zone II – R= 15 km. The population density of birds points was calculated in points, the status of stay, seasonal fluctuations in the number and species diversity of avifauna and the intensity of the ornithological situation were revealed.Despite the rather high species diversity and significant fluctuations in the number of birds, ornithological intensity in zone II during the year is ‘calm’ and reaches the upper limit of the ‘satisfactory’ level occasionally on certain days of late summer – early autumn. A place of increased concentration of birds within airport area II is an urban landfill. The decision to move the landfill beyond a 50 km radius from the runway, the prevention of nesting of aircraft‐dangerous bird species within zone II and the use of visual repellents will allow maintenance of a low level of ornithological intensity throughout the year.